Continuation of perforating branch of fibular artery as dorsalis pedis artery - Baxla, Monica; Nath, Matangeshwar (International Journal of Research in Medical Sciences, 2018)
For the effective management of vascular surgeries such as arterial cannulation, bypass surgery, percutaneous trans arterial catheterization etc. needs a sound knowledge of the vessels of the lower extremity, their branching pattern, course followed by them and their diameter. The knowledge of arterial variation is a must before a surgeon deals with the concerned area. We are reporting a case in which the perforating branch of fibular artery passes through the gap in the interosseous membrane and continues as the dorsalis pedis artery. Normally anterior tibial artery, a branch of popliteal artery is the main artery of the extensor compartment of the lower limb which continues on the dorsum of foot as dorsalis pedis artery but in this case, it became hypoplastic and disappeared below, proximal to the ankle joint.